Interface between Climate Change and National Security Threat - Bhattarai, Kamaldev (Journal of Foreign Affairs, 2023)
Climate change has emerged as an existential threat to the planet and humanity. It is fueling natural disasters, migration, energy, and health and food crises across the globe. Flood, sea-level rise, intense wildfire, heat wave, hurricanes, precipitation are threatening both civilian lives and vital infrastructure. Put together, they all have a potential to create security threats, and no country is immune from it. In June 2022, much of Pakistan was inundated by heavier than usual monsoon rain. More than 1,700 people perished and properties worth billions were destroyed in the disaster, which also triggered food and energy crises in its wake. Likewise, on June 15, 2021, Melamchi Bazar of Sindupalchok district in Nepal was ravaged by a flash flood that claimed five lives — dozens of people are still missing. It damaged several private and public properties, and damaged the infrastructure of the Melamchi Water Supply Project (Annapurna Express 2022). The above incidents show the extent of vulnerability posed by climate change-related disasters on human lives and settlements. With this context in place, this essay tries to explore the new risks posed by the effects of climate change to Nepal’s security landscape, as well as the preparations made so far to deal with possible crises. It will offer some policy recommendations.